The Triassic Mercia Mudstone Group: Sealing the UK's net zero future - Jonathon A. McEvoy; Richard H. Worden; Joshua Griffiths; Nicholas T. Smith; Daniel R. Faulkner; Samuel T.J. Jones; Holly J. Mills; Kevin G. Taylor (Earth-Science Reviews, 2026)

Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Effects of maternal arsenic exposure on birth outcomes using harmonized data across three birth cohorts - Zlatan Feric; Daniel Beene; Antonio J. Signes-Pastor; Deborah J. Watkins; Griffith Gao; Margaret R. Karagas; Debra A. MacKenzie; David R. Kaeli; Justin Manjourides (Toxicology and Environmental Health Sciences, 2026)
Objectives To assess the association between urinary arsenic concentrations and birth outcomes by harmonizing data from three independent birth cohorts. Methods We harmonized and analyzed data from the Navajo Birth Cohort Study (NBCS), the New Hampshire Birth Cohort Study (NHBCS), and the PROTECT Center study based on Puerto Rico. Birth outcomes of interest included birth weight, head circumference, birth length, gestational age at delivery, incidence of preterm birth, and size for gestational age. Urinary arsenic concentrations were used as the primary exposure metric. Harmonization involved aligning variable formats, adjusting for differences in laboratory methods, and excluding incompatible covariates, such as income and race. Results Harmonization increased the total sample size ( N = 3222) across cohorts. However, pooled analyses did not consistently demonstrate increased statistical power. Effect estimates for arsenic exposure were attenuated in some cases, and confidence intervals remained wide or even expanded relative to individual cohort analyses. Differences in biospecimen collection and laboratory assay methods required cohort-specific adjustments. Due to missing arsenic speciation data, the PROTECT cohort was excluded from two exposure models. Variability across cohorts limited the interpretability and precision of pooled estimates despite harmonization efforts. Conclusions While harmonizing data across multiple cohorts increased the sample size, it did not necessarily enhance statistical power or strengthen observed associations. Differences in data collection, laboratory methods, and available covariates posed significant challenges. These findings underscore the need for caution when interpreting pooled results from heterogeneous sources and highlight the importance of prospective planning for data harmonization in multi-cohort studies.

3D Texture Analysis of the Corpus Callosum in T1-Weighted MR Images of Children with a Traumatic Brain Injury - Jan Novak; Ahmed E. Fetit; Daniel Griffiths-King; Cathy Catroppa; Vicki A. Anderson; Amanda G. Wood (Brain Topography, 2026)
Investigating traumatic brain injuries (TBI) in the developing brain is a challenging task. The superposition of an injury to the normal development trajectory can lead to brain impairments which are not obvious at diagnosis. T1-weighted MRI, acquired routinely post-injury, has the potential to better inform diagnosis, but is limited by qualitative assessment by radiologists. Using T1-weighted volume images, we investigated the use of three-dimensional texture analysis (TA) on regions of the corpus callosum (CC) in children with TBI and typically developing controls (TDCs) in conjunction with analysis of diffusion weighted image (DWI)-derived metrics. Nineteen TDCs and 37 participants with TBI were included in the study. T1 textural metrics were extracted from the splenium, genu and body of the CC and assessed for differences between the groups. Textural skewness was found to be significantly higher in children with TBI than TDCs in the body of the CC (t-test: p < 0.004, effect size: g = 0.91) and significant differences were observed in the genu of the CC (grey level co-occurrence matrix and Grey-level run length matrix, p < 0.004, effect sizes > 0.6). Non-significant reductions in ADC were found between TBI and TDC groups in the body and the splenium of the CC. Interestingly, no differences were found between TDCs and the TBI sample using FA. The results suggest that TA can potentially be used to assess white matter integrity after paediatric TBI.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Alkali-mediated Sr incorporation mechanism and binding capacity of alkali aluminosilicate hydrate in geopolymers - Daniel A. Geddes; Martin C. Stennett; Tom J. Wilkinson; Benjamin E. Griffith; John V. Hanna; John L. Provis; Brant Walkley (Journal of Hazardous Materials, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

Competing values, ideologies and lock-in dependencies in sociotechnical pathways for industrial decarbonization - Benjamin K. Sovacool; Steve Griffiths; Hans Jakob Walnum; Dylan Daniel Furszyfer; Marfuga Iskandarova (Environmental Science & Policy, 2025)

Animal social networks are robust to changing association definitions - Alex Hoi Hang Chan; Jamie Dunning; Kristina B Beck; Terry Burke; Heung Ying Janet Chik; Daniel Dunleavy; Tim Evans; André Ferreira; Babette Fourie; Simon C. Griffith; Friederike Hillemann; Julia Schroeder (Behavioral Ecology and Sociobiology, 2025)
The interconnecting links between individuals in an animal social network are often defined by discrete, directed behaviours, but where these are difficult to observe, a network link (edge) may instead be defined by individuals sharing a space at the same time, which can then be used to infer a social association. The method by which these associations are defined should be informed by the biological significance of edges, and therefore often vary between studies. Identifying an appropriate measure of association remains a challenge to behavioural ecologists. Here, we use automatically recorded feeder visit data from four bird systems to compare three methods to identify a social association: (1) strict time-window, (2) co-occurrence in a group, and (3) arrival-time. We tested the similarity of the resulting networks by comparing the repeatability and sensitivity of individuals’ social traits (network degree, strength, betweenness). We found that networks constructed using different methods but applying similar, ecologically relevant definitions of associations based on individuals’ spatio-temporal co-occurrence, showed similar characteristics. Our findings suggest that the different methods to construct animal social networks are comparable, but result in subtle differences driven by species biology and feeder design. We urge researchers to carefully evaluate the ecological context of their study systems when making methodological decisions. Specifically, researchers in ecology and evolution should carefully consider the biological relevance of an edge in animal social networks, and the implications of adopting different definitions.

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Self-correlated spatial random variables: From an auto- to a sui- model respecification - Daniel A. Griffith (Spatial Statistics, 2024)

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Wind dispersed tree species have greater maximum height - Ferry Slik; Bruno X. Pinho; Daniel M. Griffith; Edward Webb; Akhilesh Singh Raghubanshi; Adriano C. Quaresma; Aida Cuni Sanchez; Aisha Sultana; Alexandre F. Souza; Andreas Ensslin; Andreas Hemp; Andrew Lowe; et al. (Global Ecology and Biogeography, 2024)
Aim We test the hypothesis that wind dispersal is more common among emergent tree species given that being tall increases the likelihood of effective seed dispersal. Location Americas, Africa and the Asia‐Pacific. Time period 1970–2020. Major taxa studied Gymnosperms and Angiosperms. Methods We used a dataset consisting of tree inventories from 2821 plots across three biogeographic regions (Americas, Africa and Asia‐Pacific), including dry and wet forests, to determine the maximum height and dispersal strategy of 5314 tree species. A web search was used to determine whether species were wind‐dispersed. We compared differences in tree species maximum height between biogeographic regions and examined the relationship between species maximum height and wind dispersal using logistic regression. We also tested whether emergent tree species, that is species with at least one individual taller than the 95% height percentile in one or more plots, were disproportionally wind‐dispersed in dry and wet forests within each biogeographic region. Results Our dataset provides maximum height values for 5314 tree species, of which more than half (2914) had no record of this trait in existing global databases. We found that, on average, tree species in the Americas have lower maximum heights compared to those in Africa and the Asia Pacific. The probability of wind dispersal increased significantly with tree species maximum height and was significantly higher among emergent than non‐emergent tree species in both dry and wet forests in all three biogeographic regions. Main conclusion Wind dispersal is more prevalent in tall, emergent tree species than in non‐emergent species and may thus be an important factor in the evolution of tree species maximum height. By providing the most comprehensive dataset so far of tree species maximum height and wind dispersal strategies, this study paves the way for advancing our understanding of the eco‐evolutionary drivers of tree size.

Mitonuclear interactions impact aerobic metabolism in hybrids and may explain mitonuclear discordance in young, naturally hybridizing bird lineages - Callum S. McDiarmid; Daniel M. Hooper; Antoine Stier; Simon C. Griffith (Molecular Ecology, 2024)
Understanding genetic incompatibilities and genetic introgression between incipient species are major goals in evolutionary biology. Mitochondrial genes evolve rapidly and exist in dense gene networks with coevolved nuclear genes, suggesting that mitochondrial respiration may be particularly susceptible to disruption in hybrid organisms. Mitonuclear interactions have been demonstrated to contribute to hybrid dysfunction between deeply divergent taxa crossed in the laboratory, but there are few empirical examples of mitonuclear interactions between younger lineages that naturally hybridize. Here, we use controlled hybrid crosses and high‐resolution respirometry to provide the first experimental evidence in a bird that inter‐lineage mitonuclear interactions impact mitochondrial aerobic metabolism. Specifically, respiration capacity of the two mitodiscordant backcrosses (with mismatched mitonuclear combinations) differs from one another, although they do not differ significantly from the parental groups or mitoconcordant backcrosses as we would expect of mitonuclear disruptions. In the wild hybrid zone between these subspecies, the mitochondrial cline centre is shifted west of the nuclear cline centre, which is consistent with the direction of our experimental results. Our results therefore demonstrate asymmetric mitonuclear interactions that impact the capacity of cellular mitochondrial respiration and may help to explain the geographic discordance between mitochondrial and nuclear genomes observed in the wild.

Density data for L ake E rie benthic invertebrate assemblages from 1930 to 2019 - Lyubov E. Burlakova; Alexander Y. Karatayev; Allison R. Hrycik; Susan E. Daniel; Knut Mehler; Elizabeth K. Hinchey; Ronald Dermott; Ronald Griffiths; Lillian E. Denecke (Ecology, 2024)
Benthic invertebrates are important trophic links in food webs and useful bioindicators of environmental conditions, but long‐term benthic organism abundance data across broad geographic areas are rare and historic datasets are often not readily accessible. This dataset provides densities of benthic macroinvertebrates collected from 1930 to 2019 during surveys in Lake Erie, a Laurentian Great Lake. The surveys were funded by the governments of the United States and Canada to investigate the status and changes in the benthic community. From the total of 21 lake‐wide and basin‐wide benthic surveys conducted in Lake Erie from 1929 to 2019, we were able to acquire data for 17 surveys, including species‐level data for 10 surveys and data by higher taxonomic groups for seven surveys. Our amassed Lake Erie dataset includes data from 11 surveys (including five with species‐level data) conducted in the western basin in 1930–2019, seven surveys (six with species‐level data) in the central basin, and eight surveys (seven with species‐level data) in the eastern basin (1973–2019). This Lake Erie dataset represents the most extensive temporal dataset of benthic invertebrates available for any of the Laurentian Great Lakes. Benthic samples were collected using Ponar or Shipek bottom dredges and taxa densities were calculated as individuals per square meter using the area of the dredge. Density data are provided for taxa in the Annelida, Arthropoda, Mollusca, Cnidaria, Nemertea, and Platyhelminthes phyla. Current taxonomy was used for most groups but, in a few cases, older taxonomic names were used for consistency with historical data. Analysis of this dataset indicates that eutrophication, water quality improvement, and dreissenid introduction were the major drivers of changes in the benthic community in the western basin, while hypoxia was a major factor in the central basin, and dreissenid introduction was the most important driver in the eastern basin. Considering the rarity of high taxonomic resolution long‐term benthic data for lake ecosystems, this dataset could be useful to explore broader aspects of ecological theory, including effects of eutrophication, hypoxia, invasive species, and other factors on community organization, phylogenetic and functional diversity, and spatial and temporal scales of variation in community structure. In addition, the dataset could be useful for studies on individual species, including abundance and distribution, species co‐occurrence, and how the patterns of dominance and rarity change over space and time. Use of this dataset for academic or educational purposes is encouraged as long as this data paper is properly cited.

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Impacts of spatial imputation on location-allocation problem solutions - Dongeun Kim; Yongwan Chun; Daniel A. Griffith (Spatial Statistics, 2024)

Longleaf pine savannas reveal biases in current understanding of savanna biogeography - Stephanie Pau; Daniel M. Griffith; Nicole E. Zampieri; Jennifer Costanza (Global Ecology and Biogeography, 2023)
Biased understanding of savanna biogeography Grasslands and savannas exist across a wide range of climates. Mesic savannas, with highly variable tree densities, are particularly misunderstood and understudied in comparison to arid and semi‐arid savannas. North America contains historically extensive mesic savannas dominated by longleaf pine. Longleaf pine savannas may have once been the largest savanna type on North America, yet these ecosystems have been overlooked in global syntheses. Excluding these “Forgotten Ecosystems” from global syntheses biases our understanding of savanna biogeography and distribution. Evolutionary history and distinct climate of longleaf savannas We assessed the evolutionary history and biogeography of longleaf pine savannas. We then harmonize plot data from longleaf savannas with plot data from valuable existing global synthesis of savannas on other continents. We show that longleaf pine savannas occur in a strikingly distinct climate space compared to savannas on Africa, Australia, and South America, and are unique in having wide ranging tree basal areas. Future directions Grass‐dominated ecosystems are increasingly recognized as being ancient and biologically diverse, yet threatened and undervalued. A new synthesis of savanna ecosystems considering their full range of distributions is needed to understand their ecology and conservation status. Interestingly, the closest analogues to North American savannas and their relatives in Mesoamerica and the Caribbean may be Asian savannas, which also contain mesic fire‐driven pine savannas and have been similarly neglected in existing global syntheses.

Effects of geographically stratified random sampling initial solutions on solving a continuous surface p-median location problem using the ALTERN heuristic - Changho Lee; Daniel A. Griffith; Yongwan Chun; Hyun Kim (Spatial Statistics, 2023)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Migraine, chronic kidney disease and kidney function: observational and genetic analyses - Wenqiang Zhang; Li Zhang; Luo Yang; Chenghan Xiao; Xueyao Wu; Peijing Yan; Huijie Cui; Chao Yang; Jingwei Zhu; Xuan Wu; Mingshuang Tang; Yutong Wang; et al. (Human Genetics, 2023)
Epidemiological studies demonstrate an association between migraine and chronic kidney disease (CKD), while the genetic basis underlying the phenotypic association has not been investigated. We aimed to help avoid unnecessary interventions in individuals with migraine through the investigation of phenotypic and genetic relationships underlying migraine, CKD, and kidney function. We first evaluated phenotypic associations using observational data from UK Biobank ( N = 255,896). We then investigated genetic relationships leveraging genomic data in European ancestry for migraine ( N case / N control = 48,975/540,381), CKD ( N case / N control = 41,395/439,303), and two traits of kidney function (estimated glomerular filtration rate [eGFR, N = 567,460] and urinary albumin-to-creatinine ratio [UACR, N = 547,361]). Observational analyses suggested no significant association of migraine with the risk of CKD (HR = 1.13, 95% CI = 0.85–1.50). While we did not find any global genetic correlation in general, we identified four specific genomic regions showing significant for migraine with eGFR. Cross-trait meta-analysis identified one candidate causal variant (rs1047891) underlying migraine, CKD, and kidney function. Transcriptome-wide association study detected 28 shared expression–trait associations between migraine and kidney function. Mendelian randomization analysis suggested no causal effect of migraine on CKD (OR = 1.03, 95% CI = 0.98–1.09; P = 0.28). Despite a putative causal effect of migraine on an increased level of UACR (log-scale-beta = 0.02, 95% CI = 0.01–0.04; P = 1.92 × 10 −3 ), it attenuated to null when accounting for both correlated and uncorrelated pleiotropy. Our work does not find evidence supporting a causal association between migraine and CKD. However, our study highlights significant biological pleiotropy between migraine and kidney function. The value of a migraine prophylactic treatment for reducing future CKD in people with migraine is likely limited.

The offshore renewables industry may be better served by new bespoke design guidelines than by automatic adoption of recommended practices developed for oil and gas infrastructure: A recommendation illustrated by subsea cable design - Terry Griffiths; Scott Draper; Liang Cheng; Hongwei An; Marie-Lise Schläppy; Antonino Fogliani; David White; Stuart Noble; Daniel Coles; Fraser Johnson; Bryan Thurstan; Yunfei Teng (Frontiers in Marine Science, 2023)
Introduction There is an emerging need for the offshore renewable industry to have their own bespoke design guidelines because the associated projects and offshore facilities differ in fundamental ways to oil and gas facilities. Offshore renewable energy (ORE) facilities have already surpassed the numbers of installed facilities in the oil and gas industry by an order of magnitude and demand is forecast to continue growing exponentially. In addition ORE facilities often have different response characteristics and limit states or failure modes as well as profoundly different risk and consequence profiles given they are generally uncrewed and do not contain explosive hydrocarbon fluids which might be released into the environment. Therefore, the purpose of this paper is to advocate for licensing bodies and regulators (such as the various national PEL 114 committees) to challenge the process of automatic adoption of oil and gas design processes, while pushing for offshore renewables to be treated differently, when appropriate, with more relevant and applicable guidance. Methods To support this argument we present new bespoke design guidance developed for subsea cables based on specific modes of cable behaviour, which often differ from pipelines. We also show worked examples from recent project experience. The results from on-bottom stability analyses of a set of cables are compared between conventional oil and gas guidance following DNV-RP-F109 versus the stability using cable-optimised approaches. Results The outcomes from the ‘conventional’ oil and gas results are not simply biased compared to cable-optimised design methods, with a trend of being either conservative or unconservative. Instead, the results of the two methods are very poorly correlated. This shows that the oil and gas approach isn't simply biased when applied to cables, but is instead unreliable because it doesn't capture the underlying failure conditions. These analytical comparisons are supported by field observation - the ocean doesn't lie, and makes short work of any anthropogenic structures which are designed with inadequate appreciation of the real world conditions. Discussion To support the rapid growth of ORE, we should therefore actively pursue opportunities to rewrite the design rules and standards, so that they better support the specific requirements of ORE infrastructure, rather than legacy oil and gas structures. With more appropriate design practices, we can accelerate the roll out of ORE to meet net zero, and mitigate the climate crisis.

Towards a circular economy in virgin olive oil production: Valorization of the olive mill waste (OMW) “alpeorujo” through polyphenol recovery with natural deep eutectic solvents (NADESs) and vermicomposting - Inmaculada Carmona; Itziar Aguirre; Daniel M. Griffith; Aranzazu García-Borrego (Science of The Total Environment, 2023)

2022 taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Sergey V. Alkhovsky; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Martina Bandte; Martin Beer; Nicolas Bejerman; Éric Bergeron; et al. (Archives of Virology, 2022)

Anthropogenically driven climate and landscape change effects on inland water carbon dynamics: What have we learned and where are we going? - Rachel M. Pilla; Natalie A. Griffiths; Lianhong Gu; Shih‐Chieh Kao; Ryan McManamay; Daniel M. Ricciuto; Xiaoying Shi (Global Change Biology, 2022)
Inland waters serve as important hydrological connections between the terrestrial landscape and oceans but are often overlooked in global carbon (C) budgets and Earth System Models. Terrestrially derived C entering inland waters from the watershed can be transported to oceans but over 83% is either buried in sediments or emitted to the atmosphere before reaching oceans. Anthropogenic pressures such as climate and landscape changes are altering the magnitude of these C fluxes in inland waters. Here, we synthesize the most recent estimates of C fluxes and the differential contributions across inland waterbody types (rivers, streams, lakes, reservoirs, and ponds), including recent measurements that incorporate improved sampling methods, small waterbodies, and dried areas. Across all inland waters, we report a global C emission estimate of 4.40 Pg C/year (95% confidence interval: 3.95–4.85 Pg C/year), representing a 13% increase from the most recent estimate. We also review the mechanisms by which the most globally widespread anthropogenically driven climate and landscape changes influence inland water C fluxes. The majority of these drivers are expected to influence terrestrial C inputs to inland waters due to alterations in terrestrial C quality and quantity, hydrological pathways, and biogeochemical processing. We recommend four research priorities for the future study of anthropogenic alterations to inland water C fluxes: (1) before‐and‐after measurements of C fluxes associated with climate change events and landscape changes, (2) better quantification of C input from land, (3) improved assessment of spatial coverage and contributions of small inland waterbodies to C fluxes, and (4) integration of dried and drawdown areas to global C flux estimates. Improved measurements of inland water C fluxes and quantification of uncertainty in these estimates will be vital to understanding both terrestrial C losses and the “moving target” of inland water C emissions in response to rapid and complex anthropogenic pressures.

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Representing plant diversity in land models: An evolutionary approach to make “Functional Types” more functional - Leander D. L. Anderegg; Daniel M. Griffith; Jeannine Cavender‐Bares; William J. Riley; Joseph A. Berry; Todd E. Dawson; Christopher J. Still (Global Change Biology, 2022)
Plants are critical mediators of terrestrial mass and energy fluxes, and their structural and functional traits have profound impacts on local and global climate, biogeochemistry, biodiversity, and hydrology. Yet, Earth System Models (ESMs), our most powerful tools for predicting the effects of humans on the coupled biosphere–atmosphere system, simplify the incredible diversity of land plants into a handful of coarse categories of “Plant Functional Types” (PFTs) that often fail to capture ecological dynamics such as biome distributions. The inclusion of more realistic functional diversity is a recognized goal for ESMs, yet there is currently no consistent, widely accepted way to add diversity to models, that is, to determine what new PFTs to add and with what data to constrain their parameters. We review approaches to representing plant diversity in ESMs and draw on recent ecological and evolutionary findings to present an evolution‐based functional type approach for further disaggregating functional diversity. Specifically, the prevalence of niche conservatism, or the tendency of closely related taxa to retain similar ecological and functional attributes through evolutionary time, reveals that evolutionary relatedness is a powerful framework for summarizing functional similarities and differences among plant types. We advocate that Plant Functional Types based on dominant evolutionary lineages (“Lineage Functional Types”) will provide an ecologically defensible, tractable, and scalable framework for representing plant diversity in next‐generation ESMs, with the potential to improve parameterization, process representation, and model benchmarking. We highlight how the importance of evolutionary history for plant function can unify the work of disparate fields to improve predictive modeling of the Earth system.

Poor relationships between NEON Airborne Observation Platform data and field‐based vegetation traits at a mesic grassland - Stephanie Pau; Jesse B. Nippert; Ryan Slapikas; Daniel Griffith; Seton Bachle; Brent R. Helliker; Rory C. O’Connor; William J. Riley; Christopher J. Still; Marissa Zaricor (Ecology, 2022)
Understanding spatial and temporal variation in plant traits is needed to accurately predict how communities and ecosystems will respond to global change. The National Ecological Observatory Network’s (NEON’s) Airborne Observation Platform (AOP) provides hyperspectral images and associated data products at numerous field sites at 1 m spatial resolution, potentially allowing high‐resolution trait mapping. We tested the accuracy of readily available data products of NEON’s AOP, such as Leaf Area Index (LAI), Total Biomass, Ecosystem Structure (Canopy height model [CHM]), and Canopy Nitrogen, by comparing them to spatially extensive field measurements from a mesic tallgrass prairie. Correlations with AOP data products exhibited generally weak or no relationships with corresponding field measurements. The strongest relationships were between AOP LAI and ground‐measured LAI ( r = 0.32) and AOP Total Biomass and ground‐measured biomass ( r = 0.23). We also examined how well the full reflectance spectra (380–2,500 nm), as opposed to derived products, could predict vegetation traits using partial least‐squares regression (PLSR) models. Among all the eight traits examined, only Nitrogen had a validation of more than 0.25. For all vegetation traits, validation ranged from 0.08 to 0.29 and the range of the root mean square error of prediction (RMSEP) was 14–64%. Our results suggest that currently available AOP‐derived data products should not be used without extensive ground‐based validation. Relationships using the full reflectance spectra may be more promising, although careful consideration of field and AOP data mismatches in space and/or time, biases in field‐based measurements or AOP algorithms, and model uncertainty are needed. Finally, grassland sites may be especially challenging for airborne spectroscopy because of their high species diversity within a small area, mixed functional types of plant communities, and heterogeneous mosaics of disturbance and resource availability. Remote sensing observations are one of the most promising approaches to understanding ecological patterns across space and time. But the opportunity to engage a diverse community of NEON data users will depend on establishing rigorous links with in‐situ field measurements across a diversity of sites.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

Nitrogen and phosphorus cycling in an ombrotrophic peatland: a benchmark for assessing change - Verity G. Salmon; Deanne J. Brice; Scott Bridgham; Joanne Childs; Jake Graham; Natalie A. Griffiths; Kirsten Hofmockel; Colleen M. Iversen; Terri M. Jicha; Randy K. Kolka; Joel E. Kostka; Avni Malhotra; et al. (Plant and Soil, 2021)

Evaluating the congruence between DNA ‐based and morphological taxonomic approaches in water and sediment trap samples: Analyses of a 36‐month time series from a temperate monomictic lake - Joanna Gauthier; David Walsh; Daniel T. Selbie; Alyssa Bourgeois; Katherine Griffiths; Isabelle Domaizon; Irene Gregory‐Eaves (Limnology and Oceanography, 2021)
Paleolimnological studies are central for identifying long‐term changes, yet many studies rely on bioindicators that deposit detectable subfossils in sediments, such as diatoms and cladocerans. Emerging DNA‐based approaches are expanding the taxonomic diversity that can be investigated. However, as sedimentary DNA‐based approaches are expanding rapidly, calibration work is required to determine the advantages and limitations of these techniques. In this study, we assessed the congruence between morphological and DNA‐based approaches applied to sediment trap samples for diatoms and crustaceans using both intracellular and extracellular DNA. We also evaluated which taxa are deposited in sediment traps from the water column to identify potential paleolimnological bioindicators of environmental variations. Based on 18S rRNA gene amplicons, we developed and analyzed a micro‐eukaryotic, monthly time series that spanned 3 years and was comprised of paired water column and sediment trap samples from Cultus Lake, British Columbia, Canada. Comparisons of assemblages derived from our genetic and morphological analyses using RV coefficients revealed significant correlations for diatoms, but weaker correlations for crustaceans. Intracellular DNA reads correlated more strongly with diatom morphology, while extracellular DNA reads correlated more strongly with crustacean morphology. Additional analyses of amplicon sequence variants shared between water and sediment trap samples revealed a wide diversity of taxa to study in paleolimnology, including Ciliophora, Dinoflagellata, Chytridiomycota, Chrysophyceae, and Cryptophyceae. Partial RDAs identified significant environmental predictors of these shared assemblages. Overall, our study demonstrates the effectiveness of DNA‐based approaches to track community dynamics from sediment samples, an essential step for successful paleolimnological studies.

Yellowfin Tuna Behavioural Ecology and Catchability in the South Atlantic: The Right Place at the Right Time (and Depth) - Serena R. Wright; David Righton; Joachim Naulaerts; Robert J. Schallert; Chris A. Griffiths; Taylor Chapple; Daniel Madigan; Vladimir Laptikhovsky; Victoria Bendall; Rhys Hobbs; Doug Beare; Elizabeth Clingham; et al. (Frontiers in Marine Science, 2021)
The yellowfin tuna ( Thunnus albacares: YFT) is a widely distributed, migratory species that supports valuable commercial fisheries. Landings of YFT are seasonally and spatially variable, reflecting changes in their availability and accessibility to different fleets and metiers which, in turn, has implications for sustainable management. Understanding the dynamics of YFT behaviour and how it is affected by biological and ecological factors is therefore of consequence to fisheries management design. Archival and pop-up satellite tags (PSAT) were used in the South Atlantic Ocean around St Helena between 2015 and 2020 to collect information on the movements, foraging and locomotory behaviour of YFT. The study aimed to (1) identify vertical behaviour of YFT within St Helena’s EEZ; (2) assess the timing and depth of potential feeding events and (3) to use the information to inform on the catchability of YFT to the local pole and line fishing fleet. Results indicate that the YFT daytime behaviour shifted between shallow with high incidence of fast starts in surface waters in summer months (December to April), to deep with high incidence of strikes at depth in colder months (May to November). Catchability of YFT was significantly reduced between May and November as YFT spent more time at depths below 100 m during the day, which coincides with a reduction in the quantity of YFT caught by the inshore fleet.

Genetic analysis of endometriosis and depression identifies shared loci and implicates causal links with gastric mucosa abnormality - Emmanuel O. Adewuyi; Divya Mehta; Yadav Sapkota; Yadav Sapkota; Kosuke Yoshihara; Mette Nyegaard; Valgerdur Steinthorsdottir; Andrew P. Morris; Amelie Fassbender; Nilufer Rahmioglu; Immaculata De Vivo; Julie E. Buring; et al. (Human Genetics, 2021)

Understanding the factors limiting organic consumption: the effect of marketing channel on produce price, availability, and price fairness - Inmaculada Carmona; Daniel M. Griffith; Itziar Aguirre (Organic Agriculture, 2021)

The Utility of Satellites and Autonomous Remote Sensing Platforms for Monitoring Offshore Aquaculture Farms: A Case Study for Canopy Forming Kelps - Tom W. Bell; Nick J. Nidzieko; David A. Siegel; Robert J. Miller; Kyle C. Cavanaugh; Norman B. Nelson; Daniel C. Reed; Dmitry Fedorov; Christopher Moran; Jordan N. Snyder; Katherine C. Cavanaugh; Christie E. Yorke; et al. (Frontiers in Marine Science, 2020)
The emerging sector of offshore kelp aquaculture represents an opportunity to produce biofuel feedstock to help meet growing energy demand. Giant kelp represents an attractive aquaculture crop due to its rapid growth and production, however precision farming over large scales is required to make this crop economically viable. These demands necessitate high frequency monitoring to ensure outplant success, maximum production, and optimum quality of harvested biomass, while the long distance from shore and large necessary scales of production makes in person monitoring impractical. Remote sensing offers a practical monitoring solution and nascent imaging technologies could be leveraged to provide daily products of the kelp canopy and subsurface structures over unprecedented spatial scales. Here, we evaluate the efficacy of remote sensing from satellites and aerial and underwater autonomous vehicles as potential monitoring platforms for offshore kelp aquaculture farms. Decadal-scale analyses of the Southern California Bight showed that high offshore summertime cloud cover restricts the ability of satellite sensors to provide high frequency direct monitoring of these farms. By contrast, daily monitoring of offshore farms using sensors mounted to aerial and underwater drones seems promising. Small Unoccupied Aircraft Systems (sUAS) carrying lightweight optical sensors can provide estimates of canopy area, density, and tissue nitrogen content on the time and space scales necessary for observing changes in this highly dynamic species. Underwater color imagery can be rapidly classified using deep learning models to identify kelp outplants on a longline farm and high acoustic returns of kelp pneumatocysts from side scan sonar imagery signal an ability to monitor the subsurface development of kelp fronds. Current sensing technologies can be used to develop additional machine learning and spectral algorithms to monitor outplant health and canopy macromolecular content, however future developments in vehicle and infrastructure technologies are necessary to reduce costs and transcend operational limitations for continuous deployment in an offshore setting.

2020 taxonomic update for phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Daniela Alioto; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Simon J. Anthony; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Tomáš Bartonička; et al. (Archives of Virology, 2020)

Soil nutrients and precipitation are major drivers of global patterns of grass leaf silicification - Kathleen M. Quigley; Daniel M. Griffith; George L. Donati; T. Michael Anderson (Ecology, 2020)
Grasses accumulate high concentrations of silicon (Si) in their tissues, with potential benefits including herbivore defense, improved water balance, and reduced leaf construction costs. Although Si is one of the most widely varying leaf constituents among individuals, species, and ecosystems, the environmental forces driving this variation remain elusive and understudied. To understand relationships between environmental factors and grass Si accumulation better, we analyzed foliar chemistry of grasses from 17 globally distributed sites where nutrient inputs and grazing were manipulated. These sites span natural gradients in temperature, precipitation, and underlying soil properties, which allowed us to assess the relative importance of soil moisture and nutrients across variation in climate. Foliar Si concentration did not respond to large mammalian grazer exclusion, but significant variation in herbivore abundance among sites may have precluded the observation of defoliation effects at these sites. However, nutrient addition consistently reduced leaf Si, especially at sites with low soil nitrogen prior to nutrient addition. Additionally, a leaf‐level trade‐off between Si and carbon (C) existed that was stronger at arid sites than mesic sites. Our results suggest soil nutrient limitation favors investment in Si over C‐based leaf construction, and that fixing C is especially costly relative to assimilating Si when water is limiting. Our results demonstrate the importance of soil nutrients and precipitation as key drivers of global grass silicification patterns.

The Potential and Limitations of Diatoms as Environmental Indicators in Mid-Atlantic Coastal Wetlands - Nina Desianti; Mihaela D. Enache; Michael Griffiths; Ksawery Biskup; Austin Degen; Michael DaSilva; Daniel Millemann; Lee Lippincott; Elizabeth Watson; Andrew Gray; Daria Nikitina; Marina Potapova (Estuaries and Coasts, 2019)

Sex chromosome inversions enforce reproductive isolation across an avian hybrid zone - Daniel M. Hooper; Simon C. Griffith; Trevor D. Price (Molecular Ecology, 2019)
Across hybrid zones, the sex chromosomes are often more strongly differentiated than the autosomes. This is regularly attributed to the greater frequency of reproductive incompatibilities accumulating on sex chromosomes and their exposure in the heterogametic sex. Working within an avian hybrid zone, we explore the possibility that chromosome inversions differentially accumulate on the Z chromosome compared to the autosomes and thereby contribute to Z chromosome differentiation. We analyse the northern Australian hybrid zone between two subspecies of the long‐tailed finch ( Poephila acuticauda ), first described based on differences in bill colour, using reduced‐representation genomic sequencing for 293 individuals over a 1,530‐km transect. Autosomal differentiation between subspecies is minimal. In contrast, 75% of the Z chromosome is highly differentiated and shows a steep genomic cline, which is displaced 350 km to the west of the cline in bill colour. Differentiation is associated with two or more putative chromosomal inversions, each predominating in one subspecies. If inversions reduce recombination between hybrid incompatibilities, they are selectively favoured and should therefore accumulate in hybrid zones. We argue that this predisposes inversions to differentially accumulate on the Z chromosome. One genomic region affecting bill colour is on the Z, but the main candidates are on chromosome 8. This and the displacement of the bill colour and Z chromosome cline centres suggest that bill colour has not strongly contributed to inversion accumulation. Based on cline width, however, the Z chromosome and bill colour both contribute to reproductive isolation established between this pair of subspecies.

Prospects and challenges of environmental DNA (eDNA) monitoring in freshwater ponds - Lynsey R. Harper; Andrew S. Buxton; Helen C. Rees; Kat Bruce; Rein Brys; David Halfmaerten; Daniel S. Read; Hayley V. Watson; Carl D. Sayer; Eleanor P. Jones; Victoria Priestley; Elvira Mächler; et al. (Hydrobiologia, 2019)

Assessing earth system model predictions of C 4 grass cover in North America: From the glacial era to the end of this century - Christopher J. Still; Jennifer M. Cotton; Daniel M. Griffith (Global Ecology and Biogeography, 2019)
Aim C 4 grasses are distinct from C 3 grasses, because C 4 grasses respond in a different manner to light, temperature, CO 2 and nitrogen and often have higher resource‐use efficiencies. C 3 and C 4 grasses are typically represented in earth system models (ESMs) by different plant functional types (PFTs). The ability of ESMs to capture C 4 grass biogeography and ecology across differing time periods is important to assess, given the crucial role they play in ecosystems and their divergent responses to global change. Location North America. Time periods Last Glacial Maximum (LGM), historical modern period ( ca . 1850) and end of this century. Major taxa studied C 4 grasses. Methods Proxy data representing relative cover and productivity of C 4 grasses were collated, including carbon isotope ratios of soil carbon and animal grazer tissue, and vegetation plot data in undisturbed grasslands. We selected available model predictions of C 4 PFT percentage cover. Models were compared against one another and assessed against proxy data at key time points: the LGM, the historical modern period before widespread grassland conversion to agriculture, and the end of this century. Results We highlight large differences among model predictions of percentage C 4 grass cover across North America: all pairwise combinations have correlations 4 grass cover from proxy data, during either the LGM or the historical modern period. Models generally under‐predict percentage C 4 grass cover, particularly during the historical modern period. Main conclusions Earth system models do not accurately represent the biogeography of C 4 grasses across a range of time‐scales, and their outputs do not agree with one another. We suggest model improvements to represent this crucial functional type better, including more collection and greater integration of C 3 and C 4 grass trait data, explicit representations of tree–grass competition for water, and a greater focus on disturbance ecology.

Error propagation in spatial modeling of public health data: a simulation approach using pediatric blood lead level data for Syracuse, New York - Monghyeon Lee; Yongwan Chun; Daniel A. Griffith (Environmental Geochemistry and Health, 2018)

Herbivory and eutrophication mediate grassland plant nutrient responses across a global climatic gradient - T. Michael Anderson; Daniel M. Griffith; James B. Grace; Eric M. Lind; Peter B. Adler; Lori A. Biederman; Dana M. Blumenthal; Pedro Daleo; Jennifer Firn; Nicole Hagenah; W. Stanley Harpole; Andrew S. MacDougall; et al. (Ecology, 2018)
Plant stoichiometry, the relative concentration of elements, is a key regulator of ecosystem functioning and is also being altered by human activities. In this paper we sought to understand the global drivers of plant stoichiometry and compare the relative contribution of climatic vs. anthropogenic effects. We addressed this goal by measuring plant elemental (C, N, P and K) responses to eutrophication and vertebrate herbivore exclusion at eighteen sites on six continents. Across sites, climate and atmospheric N deposition emerged as strong predictors of plot‐level tissue nutrients, mediated by biomass and plant chemistry. Within sites, fertilization increased total plant nutrient pools, but results were contingent on soil fertility and the proportion of grass biomass relative to other functional types. Total plant nutrient pools diverged strongly in response to herbivore exclusion when fertilized; responses were largest in ungrazed plots at low rainfall, whereas herbivore grazing dampened the plant community nutrient responses to fertilization. Our study highlights (1) the importance of climate in determining plant nutrient concentrations mediated through effects on plant biomass, (2) that eutrophication affects grassland nutrient pools via both soil and atmospheric pathways and (3) that interactions among soils, herbivores and eutrophication drive plant nutrient responses at small scales, especially at water‐limited sites.

Drivers of nitrogen transfer in stream food webs across continents - Beth C. Norman; Matt R. Whiles; Sarah M. Collins; Alexander S. Flecker; Steve K. Hamilton; Sherri L. Johnson; Emma J. Rosi; Linda R. Ashkenas; William B. Bowden; Chelsea L. Crenshaw; Todd Crowl; Walter K. Dodds; et al. (Ecology, 2017)
Studies of trophic‐level material and energy transfers are central to ecology. The use of isotopic tracers has now made it possible to measure trophic transfer efficiencies of important nutrients and to better understand how these materials move through food webs. We analyzed data from thirteen 15 N‐ammonium tracer addition experiments to quantify N transfer from basal resources to animals in headwater streams with varying physical, chemical, and biological features. N transfer efficiencies from primary uptake compartments (PUCs; heterotrophic microorganisms and primary producers) to primary consumers was lower (mean 11.5%, range 100%). Total N transferred (as a rate) was greater in streams with open compared to closed canopies and overall N transfer efficiency generally followed a similar pattern, although was not statistically significant. We used principal component analysis to condense a suite of site characteristics into two environmental components. Total N uptake rates among trophic levels were best predicted by the component that was correlated with latitude, DIN:SRP, GPP:ER, and percent canopy cover. N transfer efficiency did not respond consistently to environmental variables. Our results suggest that canopy cover influences N movement through stream food webs because light availability and primary production facilitate N transfer to higher trophic levels.

Recruitment of benthic invertebrates in high Arctic fjords: Relation to temperature, depth, and season - Kirstin S. Meyer; Andrew K. Sweetman; Piotr Kuklinski; Peter Leopold; Daniel Vogedes; Jørgen Berge; Colin Griffiths; Craig M. Young; Paul E. Renaud (Limnology and Oceanography, 2017)
In the high Arctic, recruitment of hard‐bottom benthic organisms has been studied at single locations, but little is known about how it varies spatially or temporally, or how it is influenced by abiotic factors. In this study, settlement plates were simultaneously deployed at five locations in three Svalbard (Norway) fjords at depths ranging from 7 m to 215 m. Recruitment was significantly different among fjords and among locations within a fjord. Recruits at each site co‐occurred randomly even though interspecific overgrowth was observed. This finding provides further evidence that there is not necessarily a relationship between non‐random co‐occurrence and interspecific competition, such as is traditionally assumed for other isolated, island‐like habitats. We found significantly lower recruitment in an Arctic‐influenced fjord than in more Atlantic‐influenced fjords. The abundance and richness of recruits was significantly lower in fall‐winter than in spring‐summer, but the spirorbid Circeis armoricana recruited in high abundance in fall‐winter. Both the abundance and taxonomic richness of recruits declined exponentially with depth, with the hydroid Stegopoma plicatile dominating at 215 m in an Atlantic‐influenced fjord. The most abundant recruiting taxa ( C. armoricana , Semibalanus balanoides , Harmeria scutulata , Celleporella hyalina ) can be described as pioneer (early‐succession) species. Crustose coralline algae, a slow‐growing superior competitor, also recruited at one location. Recruitment in Svalbard is highly variable, both spatially and temporally, and our results show the influence of local factors such as adult species composition.

Multi‐century stasis in C 3 and C 4 grass distributions across the contiguous United States since the industrial revolution - Daniel M. Griffith; Jennifer M. Cotton; Rebecca L. Powell; Nathan D. Sheldon; Christopher J. Still (Journal of Biogeography, 2017)
Aims Understanding the functional response of ecosystems to past global change is crucial to predicting performance in future environments. One sensitive and functionally significant attribute of grassland ecosystems is the percentage of species that use the C 4 versus C 3 photosynthetic pathway. Grasses using C 3 and C 4 pathways are expected to have different responses to many aspects of anthropogenic environmental change that have followed the industrial revolution, including increases in temperature and atmospheric CO 2 , changes to land management and fire regimes, precipitation seasonality, and nitrogen deposition. In spite of dramatic environmental changes over the past 300 years, it is unknown if the C 4 grass percentage in grasslands has shifted. Location Contiguous United States of America. Methods Here, we used stable carbon isotope data (i.e. δ 13 C) from 30 years of soil samples, as well as herbivore tissues that date to 1739 CE , to reconstruct coarse‐grain C 3 and C 4 grass composition in North American grassland sites to compare with modern vegetation. We spatially resampled these three datasets to a shared 100‐km grid, allowing comparison of δ 13 C values at a resolution and extent common for climate model outputs and biogeographical studies. Results At this spatial grain, the bison tissue proxy was superior to the soil proxy because the soils reflect integration of local carbon inputs, whereas bison sample vegetation across landscapes. Bison isotope values indicate that historical grassland photosynthetic‐type composition was similar to modern vegetation. Main conclusions Despite major environmental change, comparing modern plot vegetation data to three centuries of bison δ 13 C data revealed that the biogeographical distribution of C 3 and C 4 grasses has not changed significantly since the 1700s. This is particularly surprising given the expected CO 2 fertilization of C 3 grasses. Our findings highlight the critical importance of capturing the full range of physiological, ecological and demographical processes in biosphere models predicting future climates and ecosystems.

Mutualistic interaction between dichloromethane‐ and chloromethane‐degrading bacteria in an anaerobic mixed culture - Gao Chen; Sara Kleindienst; Daniel R. Griffiths; E. Erin Mack; Edward S. Seger; Frank E. Löffler (Environmental Microbiology, 2017)
Summary The microbial mixed culture RM grows with dichloromethane (DCM) as the sole energy source generating acetate, methane, chloride and biomass as products. Chloromethane (CM) was not an intermediate during DCM utilization consistent with the observation that CM could not replace DCM as a growth substrate. Interestingly, cultures that received DCM and CM together degraded both compounds concomitantly. Transient hydrogen (H 2 ) formation reaching a maximum concentration of 205 ± 13 ppmv was observed in cultures growing with DCM, and the addition of exogenous H 2 at concentrations exceeding 3000 ppmv impeded DCM degradation. In contrast, CM degradation in culture RM had a strict requirement for H 2 . Following five consecutive transfers on CM and H 2 , Acetobacterium 16S rRNA gene sequences dominated the culture and the DCM‐degrader Candidatus Dichloromethanomonas elyunquensis was eliminated, consistent with the observation that the culture lost the ability to degrade DCM. These findings demonstrate that culture RM harbours different populations responsible for anaerobic DCM and CM metabolism, and further imply that the DCM and CM degradation pathways are mechanistically distinct. H 2 generated during DCM degradation is consumed by the hydrogenotrophic CM degrader, or may fuel other hydrogenotrophic processes, including organohalide respiration, methanogenesis and H 2 /CO 2 reductive acetogenesis.

The effect of protected areas on forest disturbance in the Carpathian Mountains 1985–2010 - Van Butsic; Catalina Munteanu; Patrick Griffiths; Jan Knorn; Volker C. Radeloff; Juraj Lieskovský; Daniel Mueller; Tobias Kuemmerle (Conservation Biology, 2017)
Protected areas are a cornerstone for forest protection, but they are not always effective during times of socioeconomic and institutional crises. The Carpathian Mountains in Eastern Europe are an ecologically outstanding region, with widespread seminatural and old‐growth forest. Since 1990, Carpathian countries (Czech Republic, Hungary, Poland, Romania, Slovakia, and Ukraine) have experienced economic hardship and institutional changes, including the breakdown of socialism, European Union accession, and a rapid expansion of protected areas. The question is how protected‐area effectiveness has varied during these times across the Carpathians given these changes. We analyzed a satellite‐based data set of forest disturbance (i.e., forest loss due to harvesting or natural disturbances) from 1985 to 2010 and used matching statistics and a fixed‐effects estimator to quantify the effect of protection on forest disturbance. Protected areas in the Czech Republic, Slovakia, and the Ukraine had significantly less deforestation inside protected areas than outside in some periods; the likelihood of disturbance was reduced by 1–5%. The effectiveness of protection increased over time in these countries, whereas the opposite was true in Romania. Older protected areas were most effective in Romania and Hungary, but newer protected areas were more effective in Czech Republic, and Poland. Strict protection (International Union for Conservation of Nature [IUCN] protection category Ia‐II) was not more effective than landscape‐level protection (IUCN III‐VI). We suggest that the strength of institutions, the differences in forest privatization, forest management, prior distribution of protected areas, and when countries joined the European Union may provide explanations for the strikingly heterogeneous effectiveness patterns among countries. Our results highlight how different the effects of protected areas can be at broad scales, indicating that the effectiveness of protected areas is transitory over time and space and suggesting that generalizations about the effectiveness of protected areas can be misleading.

Effects of caffeine on alcohol reinforcement: beverage choice, self-administration, and subjective ratings - Mary M. Sweeney; Steven E. Meredith; Daniel P. Evatt; Roland R. Griffiths (Psychopharmacology, 2017)

Identification and Potential Regulatory Properties of Evolutionary Conserved Regions (ECRs) at the Schizophrenia-Associated MIR137 Locus - Olympia Gianfrancesco; Daniel Griffiths; Paul Myers; David A. Collier; Vivien J. Bubb; John P. Quinn (Journal of Molecular Neuroscience, 2016)

Leaf thickness controls variation in leaf mass per area (LMA) among grazing-adapted grasses in Serengeti - Daniel M. Griffith; Kathleen M. Quigley; T. Michael Anderson (Oecologia, 2016)

Biogeography of Cephalopods in the Southern Ocean Using Habitat Suitability Prediction Models - José C. Xavier; Ben Raymond; Daniel C. Jones; Huw Griffiths (Ecosystems, 2016)

Biodiversity and environmental context predict dung beetle‐mediated seed dispersal in a tropical forest field experiment - Hannah M. Griffiths; Julio Louzada; Richard D. Bardgett; Wallace Beiroz; Filipe França; Daniel Tregidgo; Jos Barlow (Ecology, 2015)
Biodiversity–ecosystem functioning (BEF) literature is dominated by investigations conducted in temperate grassland ecosystems under homogenous environmental conditions. Consequently, studies concerned with the functional importance of higher trophic levels, or with the role of environmental conditions in shaping BEF relationships, are comparatively uncommon. To address this, we assessed dung beetle diversity‐functioning relationships in situ, in a field experiment in the Brazilian Amazon. Dung beetles perform a number of ecological functions in habitats across the globe; in tropical forests they play a key role in the secondary dispersal of seeds. We therefore experimentally tested how the functional diversity of dung beetle communities affects seed dispersal and how BEF relationships varied with environmental context, by replicating the experiments under contrasting soil conditions. Relationships between dung beetle diversity and function were examined using diversity indices calculated using continuous morphological traits of the individuals involved in experiments, and functioning was measured as the dispersion of artificial seeds throughout the soil profile and the probability of burial. Ninety experimental plots were established across three distinct primary forest sites. We collected, identified, and measured almost 2000 beetles, and sieved around 11 Mg of soil to quantify the dispersion of 1800 seed mimics. There was a significant effect of dung beetle functional diversity on both seed dispersion and seed burial, although this depended on environmental context, with the strength or direction of responses differing across the contrasting soils. Regardless of soil type, functional richness, but not species richness, predicted seed dispersion. We therefore advocate the use of functional diversity indices over taxonomic approaches in dung beetle‐focused BEF investigations. Furthermore, we highlight the difficulties in generalizing BEF relationships, even considering a single function within the same ecosystem.

Biogeographically distinct controls on C 3 and C 4 grass distributions: merging community and physiological ecology - Daniel M. Griffith; T. Michael Anderson; Colin P. Osborne; Caroline A. E. Strömberg; Elisabeth J. Forrestel; Christopher J. Still (Global Ecology and Biogeography, 2015)
Aim C 4 photosynthesis is an adaptation that maintains efficient carbon assimilation in high‐light, high‐temperature conditions. Due to the importance of C 4 grasses for carbon and surface energy fluxes, numerous models have been proposed to describe their spatial distribution and forecast their responses to climate change. These models often rely on broad climatic predictors (e.g. temperature and precipitation) but fail to integrate other ecologically relevant factors like disturbance and competition, which may modify realized C 3 / C 4 grass distributions. Here, we present a combined evaluation of the contribution of ecological factors and climatic predictors to realized C 3 / C 4 grass distributions. We consider multiple biogeographic regions of N orth A merica using a multisource database of over 40,000 vegetation plots. Location The conterminous U nited S tates of A merica ( USA ). Methods We identified a comprehensive pool of climatic models in the literature and used information theoretic criteria to select a primary climatic predictor of C 3 and C 4 grass distributions. Subsequently, the best model was combined with ecological predictors (e.g. fire, tree cover) using a multiple regression framework and tested within eight regions. Results Surprisingly, grass‐dominated communities across the USA exist largely in C 3 ‐ or C 4 ‐dominated states. Transitions between C 3 / C 4 dominance were best explained by models that integrated temperature and precipitation with ecological factors that varied according to region. For some regions, like E astern T emperate F orests, local ecological factors were comparable in strength to broad‐scale climatic predictors of C 3 / C 4 abundance. Main conclusion Local ecological factors modify C 3 / C 4 grass responses to broad‐scale climatic drivers in ways that manifest at regional scales. In E astern T emperate F orests, for example, C 4 grass abundances are maintained below climatic expectations where tree cover creates light limitation but above expectations where frequent fires reduce tree cover. Thus, local ecological factors, which vary among biogeographic regions, contribute to large‐scale climate disequilibrium.

Proximity to ice fields and lake depth as modulators of paleoclimate records: a regional study from southwest Yukon, Canada - Guangjie Chen; Daniel T. Selbie; Katherine Griffiths; Jon N. Sweetman; Morgan Botrel; Zofia E. Taranu; Sébastien Knops; Jennifer Bondy; Neal Michelutti; John P. Smol; Irene Gregory-Eaves (Journal of Paleolimnology, 2014)

Plant Conservation Challenges in the Bahama Archipelago - Eric Carey; Lynn Gape; B. Naqqi Manco; Dion Hepburn; Ross L. Smith; Lindy Knowles; David Knowles; Mark Daniels; Michael A. Vincent; Ethan Freid; Brett Jestrow; M. Patrick Griffith; et al. (The Botanical Review, 2014)

Vaccine immunotherapy for prostate cancer: from mice to men - David M. Lubaroff; Daniel Vaena; James A. Brown; Pamela Zehr; Karen C. Griffith; Erica Brown; Julie Eastman; Kenneth Nepple; Ambika Kattula; Richard D. Williams (Immunologic Research, 2014)

Spatial and temporal patterns of dissolved nitrogen and phosphorus in surface waters of a multi-land use basin - Daniel M. Evans; Stephen H. Schoenholtz; Parker J. Wigington; Stephen M. Griffith; William C. Floyd (Environmental Monitoring and Assessment, 2014)

Priority research questions for the UK food system - John S. I. Ingram; Hugh L. Wright; Lucy Foster; Timothy Aldred; David Barling; Tim G. Benton; Paul M. Berryman; Charles S. Bestwick; Alice Bows-Larkin; Tim F. Brocklehurst; Judith Buttriss; John Casey; et al. (Food Security, 2013)
The rise of food security up international political, societal and academic agendas has led to increasing interest in novel means of improving primary food production and reducing waste. There are however, also many ‘post-farm gate’ activities that are critical to food security, including processing, packaging, distributing, retailing, cooking and consuming. These activities all affect a range of important food security elements, notably availability, affordability and other aspects of access, nutrition and safety. Addressing the challenge of universal food security, in the context of a number of other policy goals (e.g. social, economic and environmental sustainability), is of keen interest to a range of UK stakeholders but requires an up-to-date evidence base and continuous innovation. An exercise was therefore conducted, under the auspices of the UK Global Food Security Programme, to identify priority research questions with a focus on the UK food system (though the outcomes may be broadly applicable to other developed nations). Emphasis was placed on incorporating a wide range of perspectives (‘world views’) from different stakeholder groups: policy, private sector, non-governmental organisations, advocacy groups and academia. A total of 456 individuals submitted 820 questions from which 100 were selected by a process of online voting and a three-stage workshop voting exercise. These 100 final questions were sorted into 10 themes and the ‘top’ question for each theme identified by a further voting exercise. This step also allowed four different stakeholder groups to select the top 7–8 questions from their perspectives. Results of these voting exercises are presented. It is clear from the wide range of questions prioritised in this exercise that the different stakeholder groups identified specific research needs on a range of post-farm gate activities and food security outcomes. Evidence needs related to food affordability, nutrition and food safety (all key elements of food security) featured highly in the exercise. While there were some questions relating to climate impacts on production, other important topics for food security (e.g. trade, transport, preference and cultural needs) were not viewed as strongly by the participants.

MRI volume of the medial frontal cortex predicts financial capacity in patients with mild Alzheimer’s disease - Luke E. Stoeckel; Christopher C. Stewart; H. Randall Griffith; Kristen Triebel; Ozioma C. Okonkwo; Jan A. den Hollander; Roy C. Martin; Katherine Belue; Jacquelynn N. Copeland; Lindy E. Harrell; John C. Brockington; David G. Clark; et al. (Brain Imaging and Behavior, 2013)

Workshop on the ecosystem and fisheries of the Coral Sea: an Australian perspective on research and management - Jock W. Young; A. David McKinnon; Daniela Ceccarelli; Richard Brinkman; Rodrigo H. Bustamante; Mike Cappo; Cathy Dichmont; Peter Doherty; Miles Furnas; Daniel Gledhill; Shane Griffiths; Trevor Hutton; et al. (Reviews in Fish Biology and Fisheries, 2012)

Effects of simultaneous climate change and geomorphic evolution on thermal characteristics of a shallow Alaskan lake - Jennifer R. Griffiths; Daniel E. Schindler; Laurie S. Balistrieri; Gregory T. Ruggerone (Limnology and Oceanography, 2011)
We used a hydrodynamics model to assess the consequences of climate warming and contemporary geomorphic evolution for thermal conditions in a large, shallow Alaskan lake. We evaluated the effects of both known climate and landscape change, including rapid outlet erosion and migration of the principal inlet stream, over the past 50 yr as well as future scenarios of geomorphic restoration. Compared to effects of air temperature during the past 50 yr, lake thermal properties showed little sensitivity to substantial (~60%) loss of lake volume, as the lake maximum depth declined from 6 m to 4 m driven by outlet erosion. The direction and magnitude of future lake thermal responses will be driven largely by the extent of inlet stream migration when it occurs simultaneously with outlet erosion. Maintaining connectivity with inlet streams had substantial effects on buffering lake thermal responses to warming climate. Failing to account for changing rates and types of geomorphic processes under continuing climate change may misidentify the primary drivers of lake thermal responses and reduce our ability to understand the consequences for aquatic organisms.

Influences of Spatial Scale and Soil Permeability on Relationships Between Land Cover and Baseflow Stream Nutrient Concentrations - F. Bernard Daniel; Michael B. Griffith; Michael E. Troyer (Environmental Management, 2010)

Climate Change Adaptation for the US National Wildlife Refuge System - Brad Griffith; J. Michael Scott; Robert Adamcik; Daniel Ashe; Brian Czech; Robert Fischman; Patrick Gonzalez; Joshua Lawler; A. David McGuire; Anna Pidgorna (Environmental Management, 2009)

Land use change in Southern Romania after the collapse of socialism - Tobias Kuemmerle; Daniel Müller; Patrick Griffiths; Marioara Rusu (Regional Environmental Change, 2009)

Risk remaining from fine particle contaminants after vacuum cleaning of hard floor surfaces - Andrew Hunt; David L. Johnson; J. Brooks; Daniel A. Griffith (Environmental Geochemistry and Health, 2008)

Geographic sampling of urban soils for contaminant mapping: how many samples and from where - Daniel A. Griffith (Environmental Geochemistry and Health, 2008)

Integrating Agricultural Landscapes with Biodiversity Conservation in the Mesoamerican Hotspot - CELIA A. HARVEY; OLIVER KOMAR; ROBIN CHAZDON; BRUCE G. FERGUSON; BRYAN FINEGAN; DANIEL M. GRIFFITH; MIGUEL MARTÍNEZ‐RAMOS; HELDA MORALES; RONALD NIGH; LORENA SOTO‐PINTO; MICHIEL VAN BREUGEL; MARK WISHNIE (Conservation Biology, 2008)

Geography of asbestos contamination near the World Trade Center site - William C. Thayer; Daniel A. Griffith; Gary L. Diamond (Stochastic Environmental Research and Risk Assessment, 2007)

Medical geography as a science of interdisciplinary knowledge synthesis under conditions of uncertainty - Daniel A. Griffith; George Christakos (Stochastic Environmental Research and Risk Assessment, 2007)

Brain Proton MRS is Correlated with Financial Abilities in Patients with Alzheimer’s Disease - H. Randall Griffith; Ozioma C. Okonkwo; Jan A. den Hollander; Katherine Belue; Sara Lanza; Lindy E. Harrell; John C. Brockington; David G. Clark; Daniel C. Marson (Brain Imaging and Behavior, 2007)

Effects of an increase in summer precipitation on leaf, soil, and ecosystem fluxes of CO2 and H2O in a sotol grassland in Big Bend National Park, Texas - Lisa Patrick; Jessica Cable; Daniel Potts; Danielle Ignace; Greg Barron-Gafford; Alden Griffith; Holly Alpert; Natasja Van Gestel; Traesha Robertson; Travis E. Huxman; John Zak; Michael E. Loik; et al. (Oecologia, 2007)

Modeling Sustainability of Arctic Communities: An Interdisciplinary Collaboration of Researchers and Local Knowledge Holders - Jack A. Kruse; Robert G. White; Howard E. Epstein; Billy Archie; Matt Berman; Stephen R. Braund; F. Stuart Chapin; Johnny Charlie; Colin J. Daniel; Joan Eamer; Nick Flanders; Brad Griffith; et al. (Ecosystems, 2004)

Longitudinal stratification of gait economy in young boys and girls: the locomotion energy and growth study - Jennifer L. Caputo; Daniel J. Keefer; Ian S. Craig; Kelly B. Griffith; Mary Beth Akins; Gareth E. Griffith; Gary S. Krahenbuhl; Philip E. Martin; Don W. Morgan; Wayland Tseh (European Journal of Applied Physiology, 2004)

Spatial error propagation when computing linear combinations of spectral bands: The case of vegetation indices - Giuseppe Arbia; Daniel A. Griffith; Robert P. Haining (Environmental and Ecological Statistics, 2003)

A reply to Heuvelink's comments - Giuseppe Arbia; Daniel A. Griffith; Robert P. Haining (Environmental and Ecological Statistics, 2003)

Post‐Agricultural Succession in El Petén, Guatemala - Bruce G. Ferguson; John Vandermeer; Helda Morales; Daniel M. Griffith (Conservation Biology, 2003)
We compared post‐agricultural succession across the range of farming activities practiced in Guatemala's northern lowlands: agroforestry, swidden, ranching, and input‐intensive monocultures. At 10 sites over 13 to 40 months we assessed the following characteristics of trees and shrubs that were>1 cm diameter at breast height: height, basal‐area accumulation, recruitment of all individuals and fleshy‐fruited individuals, and accumulation of all species and fleshy‐fruited species. Succession, as measured by all these response variables except height, was dramatically faster on agroforestry and swidden sites than on pastures or input‐intensive monocultures. Overall recruitment was faster for swiddens than for agroforests, but other response variables did not differ significantly between the two treatments. Regression results suggest that initial ground cover by herbs inhibited recruitment of woody colonists. The significant positive coefficient for initial basal area and the significant negative coefficient for distance from forest for accumulation of both fleshy‐fruited individuals and species are probably explained by the behavioral responses of seed‐dispersing animals. Our results suggest that the conservation strategy of discouraging swidden agriculture in favor of sedentary, input‐intensive agriculture to relieve pressure on old‐growth forest may be counterproductive over the long term.

Pseudomonas aeruginosa O‐antigen chain length is determined before ligation to lipid A core - Craig Daniels; Corrie Griffiths; Bryony Cowles; Joseph S. Lam (Environmental Microbiology, 2002)
Summary Pseudomonas aeruginosa is a Gram‐negative opportunistic pathogen that infects immunocompromised patients and trauma victims and causes fatal lung infections in people with cystic fibrosis. This microorganism produces a number of virulence factors, one of which is lipopolysaccharide (LPS), which has been shown to mediate many biological effects including resistance to serum killing and phagocytosis. These biological activities have been correlated to the length of the O‐polysaccharide and its distribution on the outer membrane. Wzz is responsible for regulation of the size distribution of the O‐antigen. Wzz has been found to participate solely in the Wzy‐dependent pathway for LPS biosynthesis, which produces heteropolymeric O‐polysaccharide such as the B‐band LPS of P. aeruginosa . Our laboratory has previously reported characterization of a Wzz protein encoded in the B‐band O‐antigen biosynthesis cluster of PAO1. The availability of the genome sequence of P. aeruginosa PAO1 has made it possible to identify a second functional Wzz protein (PA0938, Wzz 2 ). Gene replacement was used to generate an unmarked wzz 2 Δ knock‐out and a wzz 2 Δ / wzz 1 ::Gm double knock‐out. As expected, the wzz 2 Δ strain produced LPS with modal length imparted by Wzz 1 , and the wzz 2 Δ / wzz 1 ::Gm strain produced LPS O‐antigen with a non‐modal (random) length. Both wzz 1 and wzz 2 from P. aeruginosa PAO1 were cloned and expressed with an N‐terminal His 6 tag. His 6 ‐Wzz 1 and His 6 ‐Wzz 2 were purified to near homogeneity by immobilized metal affinity chromatography (IMAC). These preparations were used to develop specific polyclonal antibodies against each of the proteins. In vivo protein cross‐linking followed by Western immunoblotting indicated that Wzz 1 forms dimers whereas Wzz 2 forms octamers. By generation of a wzz 2 Δ / rmlC double mutant and analysis of the LPS, we have made the novel observation that polymerization of modal chain length‐distributed O‐antigen occurred before ligation to the lipid A core. We have shown an association between the Wzz proteins and O‐antigen polymer chains using immunoprecipitation with anti‐O5 O‐antigen monoclonal antibody MF15‐4. Both Wzz 1 and Wzz 2 could be co‐precipitated with O5 polymer.

Agroforestry: a Refuge for Tropical Biodiversity after Fire - Daniel M. Griffith (Conservation Biology, 2000)